2019
DOI: 10.1016/j.jsams.2018.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends in muscular fitness of English 10-year-olds 1998–2014: An allometric approach

Abstract: Downward temporal trends in muscular fitness appear independent of secular changes in body size. We found a decrease in self-reported physical activity concurrent with the accelerated declines in fitness from 2008 to 2014. These findings suggest the declines in children are not engaging in physical activities which support development of muscular fitness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
71
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 28 publications
9
71
1
1
Order By: Relevance
“…A majority of the studies monitoring muscular fitness trends over time have focused on children. Most of these studies show a decreasing trend in muscular fitness, 10,11,[21][22][23] although, similar to the present study findings, no changes have also been observed, 24,25 while one study reported an increase. 26 Furthermore, the mean sit-up results were 37 reps/ min for 18-20 years Finnish men 7 and 34-38 repetitions in present 5-10 years older study sample.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…A majority of the studies monitoring muscular fitness trends over time have focused on children. Most of these studies show a decreasing trend in muscular fitness, 10,11,[21][22][23] although, similar to the present study findings, no changes have also been observed, 24,25 while one study reported an increase. 26 Furthermore, the mean sit-up results were 37 reps/ min for 18-20 years Finnish men 7 and 34-38 repetitions in present 5-10 years older study sample.…”
Section: Discussionsupporting
confidence: 85%
“…In the current literature, there is a lack of data on temporal trends in muscular fitness, although muscular fitness is closely linked to health outcomes . Similar to cardiorespiratory fitness, the majority of existing studies monitoring muscular fitness trends over time have focused on children . In Finland, the prevalence of young adult men with good or excellent muscular fitness decreased between 1992 and 2004 and plateaued thereafter in young adult men.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This supports the suggested year on year decline in PA currently witnessed in boys between the ages of 5 and 15, when measured by accelerometery [10]. Furthermore, recent evidence suggests there is a downward temporal trend in muscular fitness among English school children, indicating a lack of activities that support the development of muscular fitness [11]. Muscular fitness is assessed by measuring performance in tests of muscular strength, power and muscular endurance [11].…”
Section: Introductionsupporting
confidence: 62%
“…There is also an international downward temporal trend in muscular fitness among school children, indicating a lack of activities that support the development of muscular fitness [12][13][14][15]. Muscular fitness is assessed by measuring performance in tests of muscular strength, power, and muscular endurance [12], and forms part of the MBSE guideline for PA. Lower levels of muscular fitness are associated with the development of noncommunicable disease in adolescent populations [16][17][18][19][20][21]. Moreover, the development of muscular fitness has been correlated with enhanced bone health, enhanced motor skill, and decreased fat mass in adolescents [22][23][24].…”
Section: Protocol and Registrationmentioning
confidence: 99%